Pulmonary extramedullary haematopoiesis. (5th December 2011) - Mubarak, Veenu; Fanning, Stephen; Windsor, Morgon; Duhig, Edwina; Bowler, Simon
Abstract : A 72-year-old Caucasian lady with myeloproliferative disorder was admitted for evaluation of progressive dyspnoea, weight loss, fatigue and mild hypoxia. A diffuse ground glass opacity was seen on CT pulmonary angiogram. Differential diagnoses included heart failure, infection, progression of myeloproliferative disorder with extramedullary haematopoiesis, thromboembolism or hydroxyurea-induced lung injury. Bronchoscopy and broncho-alveolar lavage were uninformative however lung biopsy with video-assisted thoracoscopy revealed extramedullary haematopoiesis within lung parenchyma. This is a very rare complication of myeloproliferative disorder and the authors discuss the significance of the case, review the literature and report the patient's progress.